2016
DOI: 10.15252/embj.201592862
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria are required for pro‐ageing features of the senescent phenotype

Abstract: Cell senescence is an important tumour suppressor mechanism and driver of ageing. Both functions are dependent on the development of the senescent phenotype, which involves an overproduction of pro‐inflammatory and pro‐oxidant signals. However, the exact mechanisms regulating these phenotypes remain poorly understood. Here, we show the critical role of mitochondria in cellular senescence. In multiple models of senescence, absence of mitochondria reduced a spectrum of senescence effectors and phenotypes while p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
560
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 602 publications
(637 citation statements)
references
References 67 publications
24
560
3
1
Order By: Relevance
“…Mitochondrial dysfunction is obligatory for SASP production and cellular senescence (Correia‐Melo et al, 2016; Hutter et al, 2004). To examine mitochondrial bioenergetics, we performed high‐resolution respirometry to yield accurate quantitative measurements of oxidative phosphorylation in response to specific substrates for complex I, complex II, fat oxidation, and electron‐transfer system (ETS) capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial dysfunction is obligatory for SASP production and cellular senescence (Correia‐Melo et al, 2016; Hutter et al, 2004). To examine mitochondrial bioenergetics, we performed high‐resolution respirometry to yield accurate quantitative measurements of oxidative phosphorylation in response to specific substrates for complex I, complex II, fat oxidation, and electron‐transfer system (ETS) capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial mass increased following Tyr stimulation, as shown by the mitochondrial DNA copy number using mitoCytb and mitoNd1 (Figure 3a). Since previous studies have shown that increased mitochondrial biogenesis was part of the senescent phenotype, we measured the expression levels of its main transcriptional co‐activators, PGC‐1α and PGC‐1β (Correia‐Melo et al, 2016). mRNA analysis showed that PGC‐1β expression was increased with Tyr, while PGC‐1α was unchanged (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, mitochondrial dysfunction through ROS accumulation likely contributes to DDR establishment and senescence. In a previous study, Correia‐Melo et al (2016) reported that mitochondria were necessary for replicative and irradiation‐induced premature senescence in fibroblasts. In this case, they also observed mitochondrial ROS accumulation and increased mitochondrial mass, but the main drivers of senescence were mitochondrial biogenesis and PGC‐1β activation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations